Urban Multiculture and Everyday Encounters in Semi-Public, Franchised Cafe Spaces. Issue 3 (August 2015) - Jones, Hannah; Neal, Sarah; Mohan, Giles; Connell, Kieran; Cochrane, Allan; Bennett, Katy
This paper engages with an emergent literature on multiculture and concepts such as conviviality and negotiation to explore how increasingly ethnically diverse population routinely share and mix in urban places and social spaces. As part of a wider ESRC funded, two-year qualitative study of changing social life and everyday multiculture in different geographical areas of contemporary England, this paper draws on participant observation data from three branches of franchised leisure and consumption cafe spaces. We pay particular attention to the ways these spaces work as settings of encounter and shared presence between groups often envisaged as separated by ethnic difference. Our findings suggest that corporate spaces which are more often dismissed as commercial, globalized spaces of soulless homogeneity can be locally inflected spaces whose cultural blandness may generate confident familiarity, ethnic mixity, mundane co-presence and inattentive forms of conviviality.